The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmicb.2020.00545
|View full text |Cite
|
Sign up to set email alerts
|

XynDZ5: A New Thermostable GH10 Xylanase

Abstract: Xylanolytic enzymes have a broad range of applications in industrial biotechnology as biocatalytic components of various processes and products, such as food additives, bakery products, coffee extraction, agricultural silage and functional foods. An increasing market demand has driven the growing interest for the discovery of xylanases with specific industrially relevant characteristics, such as stability at elevated temperatures and in the presence of other denaturing factors, which will facilitate their inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…In addition, hydrolysis products, xylose, and xylobiose, identified in activity assays indicate that it acts on the ends of the xylan ( Figure 8 ). The identification of xylobiose and xylose suggests that this enzyme has exo -activity, as has been previously observed with the thermostable xylanase of Thermoanarobacterium species ( Zarafeta et al, 2020 ). These substrates derived from xylan hydrolysis are compounds of easy assimilation and can be used by other symbionts present in the intestine and by insects.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, hydrolysis products, xylose, and xylobiose, identified in activity assays indicate that it acts on the ends of the xylan ( Figure 8 ). The identification of xylobiose and xylose suggests that this enzyme has exo -activity, as has been previously observed with the thermostable xylanase of Thermoanarobacterium species ( Zarafeta et al, 2020 ). These substrates derived from xylan hydrolysis are compounds of easy assimilation and can be used by other symbionts present in the intestine and by insects.…”
Section: Discussionsupporting
confidence: 76%
“…According to previous publications, similar xylanases active at elevated temperatures and alkaline pH have ever been reported. For instance, XynDZ5, a newly reported thermostable xylanolytic enzyme derived from Thermoanaerobacterium thermosaccharolyticum , performs best at 65–75°C and pH 7.5 (Zarafeta et al, 2020 ). Another xylanase XynHB originating from B. pumilus HBP8 was extracellular secreted expressed in E. coli , which have showed high activity under alkaline conditions at 70°C (Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data available, it can be assumed that for xylanase I, a substrate concentration of 2.5% provides the highest activities, while for xylanase II no possible substrate inhibition was observed in the measured range. Similar behavior could be observed for the heterologous expressed XynDZ5 GH10 xylanase from Thermoanaerobacterium sp., where three different xylan sources were used, showing about 10-fold increase of activity if 30 g/L (3%) was used instead 0.3% ( Zarafeta et al, 2020 ). Substrate affinity of xylanase II 6.71 ± 3.14 g/L was comparable to literature values of 0.7–6.6 g/L ( Li et al, 2006 , 2010 ; Sharma et al, 2010 ; Ding et al, 2018 ; Yadav et al, 2018 ), while xylanase I showed a reduced affinity with a K M of 20.68 ± 8.53 g/L.…”
Section: Discussionmentioning
confidence: 99%